The activity of the Council of Liberation of Trieste (from May 17 to september 21, 1945) : with a short historical introduction. (Trieste : Council of Liberation of Trieste, 1945)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: territoriale kwesties